RESPONSE TO MUSLIMS DA'WAH ACTIVITIES' BY NON-MUSLIMS IN AKWANGA AND NASSARAWA EGGON LOCAL GOVERNMENT AREAS OF NASARAWA STATE, NIGERIA - Sule, Muhammad Maga (QiST: Journal of Quran and Tafseer Studies, 2024)
Da'wah is a duty for all Muslims; the Glorious Qur'an provides the basic principles of Da'wah methodologies to be applied by the Muslims Da'i (preacher) in the Da'wah field. This paper, therefore, attempts to provide the much-lacking information on the activities of Muslims in terms of Da'wah and in one hand the responses of the non-Muslims in Akwanga and Nassarawa Eggon Local Government Areas towards Islamic Da'wah. The paper looks into the activities of Muslim Organisations in the areas in carrying out Da'wah, Da'wah movement and also the responses of the non-Muslims towards Muslims Da'wah activities in the area. It was discovered that there is negative thought toward Muslims and the Da'wah message from the non-Muslims. This is crucial because necessary actions could then be taken or solution is sought to ensure the smooth progress of Da'wah activities in Akwanga and Nassarawa Eggon. This paper is adopted qualitative techniques to elicit primary data from the participants. And the researcher purposively selected ten (10) participants and were interviewed based on the issue investigated.